The Mobile Payment Acceptance Model of Chinese Residents - Chen, Shulan; Chaiyasoonthorn, Wornchanok; Chaveesuk, Singha (My University, 2021)
The rapid development of the Internet in China has changed the modes of payment among the Chinese residents. Nowadays, the mobile payment users in China take up 60.93% of the Chinese population. However, there are still 416 million non-netizens in China. In the future, China's mobile payment market will seek further expansion. In addition, with the further development of digitalization and the circulation of the digital RMB, the Chinese mobile payment, which is represented by Alipay and WeChat Pay, will suffer from huge impacts. In this paper, based on the technology acceptance model, planned behavior theory, system security, trust, and demographics, a conceptual framework is established to analyze the acceptance of mobile payment in China and find out the determinants that affect the use of mobile payment. The outcome of this paper not only provides a theoretical framework for subsequent scholars to further study the determinants of Chinese residents' mobile payment, but also provides a theoretical basis for mobile payment operators to retain and expand the mobile payment market.
Keywords: Demographics; Mobile payment acceptance model; System security; TAM; TPB; Trust